Can Education Change Society? by Michael W. Apple. Routledge: New York, 2012 - Sharma, Poonam (Voices of Teachers and Teacher Educators, 2020)
Can education change society? It depends, says Michael Apple in his book title with the question mark. He suggests that such questions never have simple answers as these are not independent questions that can be answered without context. Questions should allow complex thinking to emerge. He suggests the need to think through questions like; who teaches? What is being taught? how it is taught and assessed? and subsequently how the knowledge learnt is being used and for what purpose, by whom?